PERSONALITY DEVELOPMENT AND SOFT SKILLS - MITRA K BARUN; MITRA BASUNDHARA (NEW DELHI OXFORD UNIVERSITY PRESS, 2024)
The book Personality Development and Soft Skills by Barun K. Mitra (often co-authored with Basundhara Mitra in later editions) is a comprehensive textbook aimed at students and young professionals to enhance their employability and success in the corporate world.
Soft Skills
Psychology
All Branches
Keywords: Personality Development; Psychology